Limitations of Current GABA Agonists in Neonatal Seizures: Toward GABA Modulation Via the Targeting of Neuronal Cl− Transport - Khanna, Arjun; Walcott, Brian P.; Kahle, Kristopher T. (Frontiers in Neurology, 2013)
Neonatal intensive care has advanced rapidly in the last 40 years, with dramatic decreases in mortality and morbidity; however, for neonatal seizures, neither therapies nor outcomes have changed significantly. Clinical and experimental studies indicate that seizures in neonates have long-term neurodevelopmental and psychiatric consequences, highlighting the need for novel drugs. Current first-line treatments targeting GABAA receptors, barbiturates and benzodiazepines, are limited in their efficacy and carry significant risks to the developing brain. Here, we review the efficacy and side effect profile of current GABA agonist therapies for neonatal seizures and suggest other treatment strategies. One promising avenue is the indirect manipulation of the GABAergic system via the modulation of neuronal Cl- gradients by targeting the cation-Cl- cotransporters (NKCC1 and KCC2) or their regulatory signaling molecules (WNK and SPAK/OSR1 kinases). Such a strategy might yield a novel class of more efficacious anti-epileptics with fewer side effects in neonates by specifically addressing disease pathogenesis. Moreover, this strategy may have ramifications for other adult seizure syndromes in which GABA excitation plays a pathogenic role, such as temporal lobe epilepsy.